2016
DOI: 10.1002/jsfa.7906
|View full text |Cite
|
Sign up to set email alerts
|

Carrot juice ingestion attenuates high fructose‐induced circulatory pro‐inflammatory mediators in weanling Wistar rats

Abstract: Carrot juice administration attenuated the high fructose diet-induced elevation of levels of circulatory FFA and pro-inflammatory mediators; MCP1 and hsCRP without affecting the adiposity and cell size of visceral fat depot; RPWAT. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…On the other hand, accumulating evidence suggested that yogurt, ingredients of diet such as fruit and vegetables are also beneficial for NAFLD. Carrot, apple, and probiotic yogurt have been suggested to benefit the NAFLD population. Therefore, based on previous research, we supposed that the results of this study are the combined effects of calorie restriction and ICR models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, accumulating evidence suggested that yogurt, ingredients of diet such as fruit and vegetables are also beneficial for NAFLD. Carrot, apple, and probiotic yogurt have been suggested to benefit the NAFLD population. Therefore, based on previous research, we supposed that the results of this study are the combined effects of calorie restriction and ICR models.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, yogurt, fruit, and vegetables also have benefit for NAFLD. Carrot juice administration attenuates the high fructose diet‐induced elevation of circulatory free fatty acid (FFA) and pro‐inflammatory mediators . It is also shown that the replacement of calories in the Western diet with apple pomace attenuated NAFLD risk …”
Section: Introductionmentioning
confidence: 99%
“…22 The activity of glycerol-3-phosphate dehydrogenase (GPDH) (EC 1.1.1.8) in RPWAT was measured, according to the method of Wise and Green. 22 The activity of glycerol-3-phosphate dehydrogenase (GPDH) (EC 1.1.1.8) in RPWAT was measured, according to the method of Wise and Green.…”
Section: )mentioning
confidence: 99%
“…15 The fatty acid desaturase (delta-9 desaturase [D9D]) activity indices (ratio of palmitoleic [C16:1] to palmitic [C16:0] acid and oleic [C18:1] to stearic [C18:0] acid; D9D-C16 and D9D-C18, respectively), the indicators of SCD1 activity, were calculated as reported earlier. 22…”
Section: Total Lipid Extraction and Fatty Acid Composition By Gas-lmentioning
confidence: 99%
See 1 more Smart Citation